Modelación de la curva de demanda a corto plazo mediante los modelos Splines, Markoviano para una óptima respuesta a la demanda. - Gutiérrez Pinto, Christian David (2018)
Finding the mathematical model that allows us to model the demand curve that represents users' consumption and manage it optimally is the main objective of this work. For which we will use two highly known mathematical models, such as: Spline and Markov. The Markovian model develops profiles of electrical demand, while the Spline algorithm uses functions that achieve smoothing of curves. The response to the electrical demand admits to manage the consumption of the energy allowing to optimize resources, in this way avoids that sources of unnecessary generation enter the system, thus avoiding that the curve of demand is modified; while, the estimation of the demand analyzes the behavior of the system in the short, medium and long term, avoiding possible failures with the purpose of reducing the probabilities that the demand curve is abruptly altered, which in turn facilitates a correct planning and operation of the system. Modeling the demand curve through the power that is delivered to consumers are extremely useful, since they allow to eliminate pronounced peaks to reduce the area under the demand curve.